Molecular dynamics simulations studies of transport properties of sodium-(polymethacrylate) (Na+-PMA) in aqueous solutions – Effect of salt concentration. (2021) - Gupta, Abhishek Kumar
Abstract: The detailed atomistic molecular dynamics simulations studies of multiple chain anionic polyelectrolyte sodium-(polymethacrylate) (Na + -PMA) was carried out to investigate the effect of monovalent salt i.e. NaCl on the transport properties such as self-diffusivity of sodium salt i.e., Na + -PMA, salt-ions and water molecules in dilute aqueous solutions. The NaCl concentration was varied from dilute (0.01 M) regime to concentrated regime (1 M) and the self-diffusivity of Na + -PMA, salt-ions and water molecules were obtained. The Na + -PMA diffusivity shows a decrease with added salt concentration in excellent agreement with related experiments and previous reported atomistic and model simulation works. The salt ions i.e. Na + and Cl − too shows a decrease in their self-diffusivity values with NaCl concentration. The self-diffusivity of water molecules was found to be decrease in a linear manner with salt concentration. The salt-ions exhibits faster movement as compared to Na + -PMA and water on account of a higher self-diffusion coefficient.